Whisky, Whiskey, and Bourbon: Products and Manufacture - Piggott, J. R. [UNESP] (Elsevier, 2015)
Whiskeys are distilled beverages that have been produced by the distillation of fermented cereals and have been matured in oak casks. They can be classified according to starting material, blending, and country of origin. The major grains used in whiskey production are maize, barley, wheat, and rye. Amylase activity required for starch breakdown is obtained from malted barley, and some regulations permit the use of other enzymes. The yeast used for the fermentation of the cereal extract is normally a specially developed strain of Saccharomyces cerevisiae. Distillation is in small pot stills or continuous column stills, followed by maturation normally for at least 3 years in oak casks.
Keywords: Barrel; Blending; Cask; Cereal; Distillation; Fermentation; Maize; Malt; Maturation; Oak; Rye; Wheat